Natural diversity in vegetative and reproductive investments of perennial ryegrass is shaped by the climate at the place of origin. (13th July 2017) - Barre, P.; Ruttink, T.; Muylle, H.; Lootens, P.; Sampoux, J.‐P.; Rohde, A.; Combes, D.; Roldán‐Ruiz, I.
Abstract: In forage grasses, vegetative and reproductive investments are major determinants of yield and persistence. A survey of the diversity of vegetative and reproductive investment traits was carried out on 213 perennial ryegrass genotypes, representing 51 natural European accessions. Plants were phenotyped for traits related to leaf elongation, tillering, reproductive investment and heading date, at two locations with markedly different climates. Strong genetic effects for all traits were found. Interactions between genotype and location were moderate. Plants showed stronger spring leaf growth, lower numbers of tillers and higher reproductive investments at Lusignan (France) than at Melle (Belgium). Plant growth rate and tillering capacity were genetically nearly independent suggesting breeding for both traits simultaneously and independently should be possible. A high genetic diversity was observed for all traits. This diversity was structured in three main clusters. One cluster comprised early‐flowering genotypes with high reproductive investments and high spring growth rates. The remaining genotypes fell into two clusters based on differences in tillering capacity. Clear links were found between traits and the climatic conditions of the region of origin of the accessions. Autumn growth rate was positively correlated with solar radiation at the region of origin in October and February.